Copper alloy material, preparation method of copper alloy material and application of copper alloy material in preparation of relay movable contact spring or electric connector
By preparing copper alloy materials containing Cr, Zr, Si and trace elements, and combining specific process parameters, the contradiction between high mechanical strength and high conductivity in relay moving spring materials has been resolved, enabling the application of copper alloy materials with high fatigue life, suitable for relay moving springs and electrical connectors.
Patent Information
- Application Number
- CN202411738890.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-10
AI Technical Summary
Existing relay moving spring materials are difficult to simultaneously possess high mechanical strength, high conductivity, and excellent fatigue performance, leading to easy fatigue damage during frequent switching operations.
The material is made of copper alloy containing Cr, Zr, Si and trace elements. It is prepared through processes such as smelting, casting, hot rolling, cold rolling and aging treatment to ensure high mechanical strength and high electrical conductivity. Fatigue performance is improved by optimizing specific process parameters such as the use of covering agents and protective atmosphere treatment.
The prepared copper alloy material has a tensile strength of 480~700MPa, a conductivity of >80%IACS, and a fatigue life of over 10 million cycles. It is suitable for relay moving springs and electrical connectors, significantly improving the overall performance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper alloys, and in particular to a copper alloy material and a preparation method thereof, and application of the copper alloy material in preparing a relay reed or an electric connector. Background Art
[0002] Relay (electromagnetic relay) is a mechanical physical switch controlled by a circuit. It is widely used in industrial control, home appliances, automation equipment and other fields for circuit switching. Electromagnetic relays generate magnetic fields through current, and the magnetic field controls the switch. There are many different types, usually working on roughly similar principles. In general electromagnetic relays, the moving reed is the carrier of load power, which plays the role of contact riveting support, interconnection and conversion. The moving reed realizes the switching of the circuit on and off by generating relative displacement, and is one of the key components of the relay. The moving reed of the relay needs to have a high fatigue life. The main reason is that the relay needs to be frequently switched during use, and the moving reed needs to be frequently bent and restored to its original state, which will cause the reed to be subjected to continuous stress and deformation, which is easy to cause fatigue damage. The structure size of the moving reed is different for different relay structures. In some small and ultra-small relays, the moving reed is thin, only about 0.12 mm, so it is required to have high physical and electrical properties.
[0003] At present, the most common material for the dynamic reed of relays is T2 copper. In addition, high-strength beryllium copper, copper-nickel-silicon alloy, etc. are also used. Generally, the tensile strength of T2 copper is about 195~395MPa, the hardness is about 60~120HV, the elastic modulus is about 115GPa, and the conductivity is about 97%IACS. The tensile strength of beryllium copper can exceed 1000MPa, but the conductivity is only about 23%IACS. For example, copper-nickel-silicon alloy C64725, which is commonly used in relays, has a tensile strength of about 450~700MPa, a hardness of about 125~230HV, an elastic modulus of about 130GPa, and a conductivity of about 46%IACS.
[0004] As a relay reed, it needs good fatigue performance. Generally, the fatigue life of T2 copper under 300Mpa stress is less than 10 5 times; copper-nickel-silicon alloy, taking C64725 commonly used in relays as an example, has a fatigue life of about 10 under 300MPa stress. 6 Secondary level; fatigue life of some beryllium copper under 300MPa stress>10 7 Second-rate.
[0005] It can be seen that the current relay reeds either have high conductivity but low mechanical strength, or high mechanical strength but low conductivity. There is still a lack of a material that has both high mechanical strength and high conductivity and excellent fatigue performance.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] A first object of the present invention is to provide a copper alloy material having high mechanical strength, high electrical conductivity and excellent fatigue performance.
[0008] A second object of the present invention is to provide a method for preparing the copper alloy material.
[0009] The third object of the present invention is to provide an application of the above copper alloy material in the preparation of a relay reed or an electrical connector.
[0010] In order to achieve the above objectives, the following technical solutions are adopted: In a first aspect, the present invention provides a copper alloy material, comprising, by mass percentage: 0.15% to 0.45% Cr, 0.05% to 0.25% Zr, 0.005% to 0.05% Si, and the balance being copper and unavoidable impurities; The mass ratio of Cr to Zr is (2:1) to (5:1); The mass ratio of Cr to Si is (10:1) to (30:1).
[0011] As a further technical solution, it also includes trace elements with a mass percentage of 0.001% to 0.15%; The trace elements include at least one of B, Mg, Ti, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y or Sc.
[0012] In a second aspect, the present invention provides a method for preparing the above copper alloy material, comprising the following steps: The materials are prepared according to the mass percentage, and then smelting, casting, hot rolling, first cold rolling, second cold rolling, third cold rolling and second aging treatment are carried out in sequence to prepare a copper alloy material; The first aging treatment is also included between the first cold rolling and the second cold rolling or between the second cold rolling and the third cold rolling.
[0013] As a further technical solution, the smelting temperature is 1270-1290°C; The casting process parameters include: casting temperature of 1220~1240°C, pulling speed of 55~65 mm / min, casting speed of 85~95 mm / min, cooling water flow of 45~70 cubic meters / hour, and crystallizer vibration frequency of 45~60 times / minute.
[0014] As a further technical solution, during the smelting process, the smelting process is covered with a graphite flake covering agent; After smelting, it is covered with graphite powder covering agent and then cast; During casting, the launder is covered with a covering agent consisting mainly of CaCO3, CaF2, and MgCO3; During the casting process, the crystallizer is protected by protective gas; The Zr element is added during the casting process.
[0015] As a further technical solution, the hot rolling temperature is 880-960°C, and the hot rolled strip is cooled by water spraying; The processing rate of the hot rolling is 85% to 95%, and the processing rate of each pass is independently 15% to 45%.
[0016] As a further technical solution, the processing rate of the first cold rolling is 85% to 95%, and the processing rate of each pass is independently 20% to 25%; The total processing rate of the second cold rolling is 55% to 95%, and the total processing rate of the third cold rolling is 10% to 30%; The processing rate of each pass of the second cold rolling is independently 20% to 35%, and the processing rate of each pass of the third cold rolling is independently 10% to 30%.
[0017] As a further technical solution, the first aging treatment and the second aging treatment are bell jar aging treatments; The bell jar aging treatment includes: heating to 400-460°C for 10-12 hours, keeping the temperature for 7-9 hours, and then cooling to below 60°C before being taken out of the furnace; The bell jar aging treatment is carried out under a protective atmosphere.
[0018] As a further technical solution, after the first aging treatment and the second aging treatment, a cleaning device is used to pickle and scrape to remove the chromium-rich oxide layer and oil stains; After the first aging treatment, the process parameters of pickling and scraping include: a cleaning speed of 20 to 35 m / min, a brush pressing current of 20A to 25A, a brush speed of 700 to 950 rpm, and a brush mesh number of 2000 to 3000 meshes; After the first aging treatment, the process parameters of pickling and scraping include: a cleaning speed of 15 to 30 m / min, a brush pressing current of 0.6A to 3.5A, a brush speed of 800 to 900 rpm, and a brush mesh size of 2000 to 3000 meshes.
[0019] In a third aspect, the present invention provides the use of the above copper alloy material in the preparation of a relay reed or an electrical connector.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The copper alloy material provided by the present invention has a tensile strength of 480-700 MPa, a yield strength of 450-600 MPa, a conductivity of more than 80% IACS, an elongation after fracture of more than 8%, a hardness of 140-210 HV, a fatigue life of more than 10 million times, and has both high mechanical strength and high conductivity characteristics. It can be used for a relay reed or an electrical connector, performs excellently in practical applications, and fills a gap in the relevant market. DETAILED DESCRIPTION
[0021] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0022] In the first aspect, the present invention provides a copper alloy material, mainly composed of Cr, Zr, Si, Cu and inevitable impurities, in which, by mass percentage, Cr may be, for example, but not limited to 0.15%, 0.3% or 0.45%; Zr may be, for example, but not limited to 0.05%, 0.15% or 0.25%; Si may be, for example, but not limited to 0.005%, 0.01% or 0.05%. The mass ratio of Cr to Zr may be, for example, but not limited to 2:1, 3:1, 4:1 or 5:1; the mass ratio of Cr to Si may be, for example, but not limited to 10:1, 20:1 or 30:1.
[0023] The inventors have found that the copper alloy material composed of the above-mentioned specific elements has a tensile strength of 480~700MPa, a yield strength of 450~600MPa, a conductivity of >80%IACS, an elongation after fracture of >8%, a hardness of 140~210HV, a fatigue life of more than 10 million times, and has high mechanical strength and high conductivity characteristics. It can be used for relay reeds or electrical connectors, performs excellently in practical applications, and fills the gap in the relevant market.
[0024] In some optional embodiments, it further comprises trace elements in an amount of 0.001% to 0.15% by mass; The trace elements include, but are not limited to, at least one of B, Mg, Ti, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y or Sc.
[0025] In a second aspect, the present invention provides a method for preparing the above copper alloy material, comprising the following steps: The materials are prepared according to the mass percentage, and then smelting, casting, hot rolling, first cold rolling, second cold rolling, third cold rolling and second aging treatment are carried out in sequence to prepare a copper alloy material; The first aging treatment is also included between the first cold rolling and the second cold rolling or between the second cold rolling and the third cold rolling.
[0026] The preparation method is simple and convenient, and the prepared copper alloy has excellent performance.
[0027] In some optional embodiments, the smelting temperature may be, for example, but not limited to, 1270° C., 1280° C. or 1290° C.; The casting process parameters include: the casting temperature can be, for example, but not limited to, 1220°C, 1230°C or 1240°C, the pulling speed is 55~65 mm / min, the casting speed is 85~95 mm / min, the cooling water flow rate is 45~70 cubic meters / hour, and the crystallizer vibration frequency is 45~60 times / minute.
[0028] In some optional embodiments, the size of the ingot obtained by casting may be, for example, 180×610 mm.
[0029] In some optional embodiments, during the smelting process, the graphite flake covering agent is used for covering; After smelting, it is covered with graphite powder covering agent and then cast; During casting, the launder is covered with a covering agent consisting mainly of CaCO3, CaF2, and MgCO3; During the casting process, the crystallizer is protected by protective gas with a pressure of 0.3~0.5MPa; In some optional embodiments, during the smelting process, the Zr element is most easily oxidized. To cope with the oxidation of the Zr element, the Zr element is preferably added to the launder during the casting process.
[0030] In some optional embodiments, the hot rolling temperature may be, for example, but not limited to, 880° C., 920° C. or 960° C., the hot rolled strip is cooled by water spraying, and the hot rolling is performed by online solution treatment; The processing rate of the hot rolling may be, for example, but not limited to, 85%, 90% or 95%, and the processing rate of each pass may be, for example, but not limited to, 15%, 30% or 45%.
[0031] In some optional embodiments, the processing rate of the first cold rolling may be, for example, but not limited to 85%, 90% or 95%, and the processing rate of each pass may be, for example, but not limited to 20%, 22% or 25% independently; The total processing rate of the second cold rolling may be, for example, but not limited to, 55%, 75% or 95%; the total processing rate of the third cold rolling may be, for example, but not limited to, 10%, 20% or 30%.
[0032] The processing rate of each pass of the second cold rolling can be, for example, but not limited to 20%, 25% or 35%, and the processing rate of each pass of the third cold rolling can be, for example, but not limited to 10%, 20% or 30%.
[0033] In some optional embodiments, the first aging treatment and the second aging treatment are bell jar aging treatments; The bell jar aging treatment includes: heating to 400-460°C for 10-12 hours, keeping the temperature for 7-9 hours, and then cooling to below 60°C before being taken out of the furnace; The bell jar aging treatment is carried out under a protective atmosphere.
[0034] In some optional embodiments, the estimated expression for the ultimate strength of the copper alloy material after solution aging treatment is σ=233.0+162.7× Cr +480.9Y Zr +64.9X Cr Y Zr 1 / 3 , X Cr ≤0.87 at.%,Y Zr ≤0.12 at.%.
[0035] In some optional embodiments, the estimated expression for the maximum conductivity of the copper alloy material after solution aging treatment is λ=100-8.1X Cr -71.5Y Zr +8.94X Cr Y Zr 1 / 3 , X Cr ≤0.87 at.%,Y Zr ≤0.12 at.%.
[0036] In some optional embodiments, after the first aging treatment and the second aging treatment, a cleaning device is used to pickle and scrape to remove the chromium-rich oxide layer and oil stains; After the first aging treatment, the process parameters of pickling and scraping include: a cleaning speed of 20 to 35 m / min, a brush pressing current of 20A to 25A, a brush speed of 700 to 950 rpm, and a brush mesh number of 2000 to 3000 meshes; After the first aging treatment, pickling (cleaning with dilute sulfuric acid, it should be noted that, unless otherwise specified, the pickling and scraping of the present invention are all cleaned with dilute sulfuric acid) The process parameters of the brushing include: a cleaning speed of 15 to 30 meters per minute, a brush pressing current of 0.6A to 3.5A, a brush speed of 800 to 900 revolutions per minute, and a brush mesh number of 2000 to 3000 meshes.
[0037] Cleaning equipment is used to remove the chromium-rich oxide layer. By designing the parameters of the cleaning equipment, the grinding and cleaning intensity is increased to remove the chromium-rich oxide layer without affecting the surface quality. Compared with other methods, such as changing the cleaning medium to hydrogen peroxide or a mixed acid of nitric acid and hydrofluoric acid, its advantage is that it can be mixed with other types of materials for production, without the need for special production equipment, and can reduce production costs and improve production efficiency.
[0038] In a third aspect, the present invention provides the use of the above copper alloy material in the preparation of a relay reed or an electrical connector.
[0039] The copper alloy material provided by the present invention has the characteristics of high mechanical strength and high electrical conductivity, and can be used for a relay reed or an electrical connector.
[0040] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0041] Example 1 The copper alloy material for the relay spring and general electrical connectors achieved in this case has a width of 85.5 mm, a thickness of 0.4 mm, and a state of H04, which is the most widely used specification state. The element composition, process parameters and performance of this embodiment are shown in Tables 1 and 2.
[0042] The process used in this case is: batching, smelting, casting, sawing → hot rolling, milling → first cold rolling, trimming → cleaning → second cold rolling → first aging, first pickling and scraping → third cold rolling → second aging, second pickling and scraping → stretching, shearing, packaging and warehousing.
[0043] Ingredients. Ingredients are prepared by mass fraction. Cr, Zr and Si are introduced in the form of CuCr10 copper-chromium master alloy (copper-chromium alloy with Cr mass ratio of 10%, the same below), CuSi20 copper-silicon master alloy and CuZr40 copper-zirconium master alloy.
[0044] Melting. First add CuSi20 copper-silicon master alloy, then add the same type of scraps, then add electrolytic copper, cover with graphite flakes, and the molten copper should not be exposed. When the temperature reaches the melting temperature of 1280℃, take samples to test the composition, and add CuCr10 copper-chromium master alloy and CuSi20 copper-silicon master alloy according to the test results. Let it stand for more than 20 minutes, take samples to test the composition, and after passing the test (if unqualified, add more and stand for more than 20 minutes), use inert gas, argon in this case, degas for 20-30 minutes, and the degassing flow rate is based on the covering layer jumping but not breaking to expose the copper water. Use dried graphite powder to cover tightly before casting, and the furnace mouth, crystallizer, launder, etc. should be baked red hot.
[0045] Casting. Casting temperature 1230℃, pulling speed 60mm / min, normal drawing speed 90mm / min, initial cooling water flow 20m3 / h, cooling water flow 60m3 / h, crystallizer vibration frequency 50 times / min, ingot size 180×610mm. During casting, the launder is covered with a covering agent composed of CaCO3, CaF2 and a small amount of MgCO3, and the crystallizer is protected by argon gas with a protective gas hood, and the argon gas pressure is [0.3,0.5]MPa.
[0046] The Zr element is added in the launder during the casting process.
[0047] The hot rolling temperature is 890℃, from 180mm to 17mm, the hot rolling processing rate is about 91%, 7 passes, and the processing rate of each pass is about 15%-45%. The hot rolled strip is cooled by water spraying, and the hot rolling is solid solution online.
[0048] Mill the surface to remove scale and various defects.
[0049] The first cold rolling is to 1.5 mm, the processing rate is about 90%, 9 passes, and the pass distribution is (unit: mm) 15→12→9.3→7.2→5.6→4.4→3.4→2.6→2→1.5.
[0050] The cutting edge retains a width of 610 mm.
[0051] After cleaning, the second cold rolling was performed to 0.56 mm, with a processing rate of about 63%. In this case, the second cold rolling was performed in 3 passes, with the pass distribution being (unit: mm) 1.5→1.1→0.8→0.56.
[0052] The first aging process is carried out after the second cold rolling. The bell jar aging process is carried out at 420℃, with an 11-hour heating process and an 8-hour insulation process. During the heating and insulation stages, the hydrogen content is 70%-80%, and the hydrogen flow rate is 8-20 cubic meters / hour. During the cooling stage, the hydrogen content is 70%-80%. The furnace temperature should not be greater than 60℃.
[0053] The first pickling and scraping. A large brush is used to press down the current, slow the cleaning speed, and use multiple pairs of brushes to grind off the Cr-rich oxide layer. The specific implementation parameters of different equipment are different. The equipment used for post-processing of the finished material in this case is specifically implemented as follows: cleaning at a speed of 30 meters per minute, the brush pressing current is 22A, the brush speed is 800 revolutions per minute, and the brush mesh is 2000-3000 mesh.
[0054] The third cold rolling was to 0.4 mm, with a processing rate of about 29%. In this case, the third cold rolling was carried out using a twenty-roller reversing mill, with 2 passes, and the pass distribution was (unit: mm) 0.56→0.46→0.4.
[0055] The total processing rate of the second and third cold rolling in this case is about 73%.
[0056] The second aging process is carried out after the third cold rolling. The bell jar aging process is carried out at 420℃, with an 11-hour heating process and an 8-hour insulation process. During the heating and insulation stages, the hydrogen content is 70%-80%, and the hydrogen flow rate is 8-20 cubic meters / hour. During the cooling stage, the hydrogen content is 70%-80%. The furnace temperature should not be greater than 60℃.
[0057] Second pickling and scraping. Use a large brush to press down the current, slow the cleaning speed, and use multiple pairs of brushes to grind off the Cr-rich oxide layer. The specific implementation parameters of different equipment are different. The equipment used for post-processing of the finished material in this case is specifically implemented as follows: cleaning at a speed of 20 meters per minute, the brush presses down the current of 2A, the brush speed is 850 revolutions per minute, and the brush mesh is 2000-3000 mesh.
[0058] After the subsequent pulling and cutting tests are passed, the products will be packaged and put into storage.
[0059] Example 2 The copper alloy material for the relay reed and general electrical connectors achieved in this case has a width of 160 mm, a thickness of 0.1 mm, and a state of H04. The element composition, process parameters, and performance of this embodiment are shown in Tables 1 and 2.
[0060] The process used in this case is: batching, smelting, casting, sawing → hot rolling, milling → first cold rolling, edge trimming → first aging, first pickling and scraping → second cold rolling → third cold rolling → coil loosening → second aging, second pickling and scraping → stretching, shearing, packaging and warehousing.
[0061] Ingredients. Ingredients are prepared in mass fractions. Cr, Zr and Si are introduced in the form of CuCr10 copper-chromium master alloy, CuSi20 copper-silicon master alloy and CuZr40 copper-zirconium master alloy.
[0062] Melting. First add CuSi20 copper-silicon master alloy, then add the same type of scraps, then add electrolytic copper, cover with graphite flakes, and the molten copper should not be exposed. When the temperature reaches the melting temperature of 1270℃, take samples to test the composition, and add CuCr10 copper-chromium master alloy and CuSi20 copper-silicon master alloy according to the test results. Let it stand for more than 20 minutes, take samples to test the composition, and after passing the test (if unqualified, add more and stand for more than 20 minutes), use inert gas, argon in this case, degas for 20-30 minutes, and the degassing flow rate is based on the covering layer jumping but not breaking to expose the copper water. Use dried graphite powder to cover tightly before casting, and the furnace mouth, crystallizer, launder, etc. should be baked red hot.
[0063] Casting. Casting temperature 1220℃, pulling speed 55mm / min, normal drawing speed 85mm / min, initial cooling water flow 10m3 / h, cooling water flow 45m3 / h, crystallizer vibration frequency 45 times / min, ingot size 180×610mm. During casting, the launder is covered with a covering agent composed of CaCO3, CaF2 and a small amount of MgCO3, and the crystallizer is protected by argon gas with a protective gas hood, and the argon gas pressure is [0.3,0.5]MPa.
[0064] The Zr element is added in the launder during the casting process.
[0065] The hot rolling temperature is 890℃, from 180mm to 17mm, the hot rolling processing rate is about 91%, 7 passes, and the processing rate of each pass is about 15%-45%. The hot rolled strip is cooled by water spraying, and the hot rolling is solid solution online.
[0066] Mill the surface to remove scale and various defects.
[0067] The first cold rolling is to 1.5 mm, the processing rate is about 90%, 9 passes, and the pass distribution is (unit: mm) 15→12→9.3→7.2→5.6→4.4→3.4→2.6→2→1.5.
[0068] The cutting edge retains a width of 610 mm.
[0069] The first aging is carried out after the first cold rolling. The bell jar aging is carried out at 420℃, with a heating process of 11 hours and a heat preservation process of 8 hours. During the heating and heat preservation stages, the hydrogen content is 70%-80%, and the hydrogen flow rate is 8-20 cubic meters / hour. During the cooling stage, the hydrogen content is 70%-80%. The furnace temperature should not be greater than 60℃.
[0070] The first pickling and scraping. A large brush is used to press down the current, slow the cleaning speed, and use multiple pairs of brushes to grind off the Cr-rich oxide layer. The specific implementation parameters of different equipment are different. The equipment used for post-processing of the finished material in this case is specifically implemented as follows: cleaning at a speed of 20 meters per minute, the brush pressing current is 20A, the brush speed is 700 revolutions per minute, and the brush mesh is 2000-3000 mesh.
[0071] The second cold rolling was to 0.19 mm, with a processing rate of about 87%. In this case, the second cold rolling was performed in 6 passes, with the pass distribution being (unit: mm) 1.5→1.01→0.7→0.5→0.36→0.26→0.19.
[0072] The third cold rolling was to 0.1 mm, with a processing rate of about 47%. In this case, the third cold rolling was carried out using a twenty-roller reversing mill, 2 passes, and the pass distribution was (unit: mm) 0.19→0.136→0.1.
[0073] The total processing rate of the second and third cold rolling in this case is about 93%.
[0074] Unwinding. For strips with a thickness of less than 0.4 mm, in order to prevent sticking after aging, cleaning equipment, continuous annealing equipment or cold rolling mills are required to unwind the strips.
[0075] The second aging process is carried out after the third cold rolling. The bell jar aging process is carried out at 420℃, with an 11-hour heating process and an 8-hour insulation process. During the heating and insulation stages, the hydrogen content is 70%-80%, and the hydrogen flow rate is 8-20 cubic meters / hour. During the cooling stage, the hydrogen content is 70%-80%. The furnace temperature should not be greater than 60℃.
[0076] Second pickling and scraping. Use a large brush to press down the current, slow the cleaning speed, and use multiple pairs of brushes to grind off the Cr-rich oxide layer. The specific implementation parameters of different equipment are different. The equipment used for post-processing of the finished material in this case is specifically implemented as follows: cleaning at a speed of 15 meters per minute, a current of 0.6A, a brush speed of 800 revolutions per minute, and a brush mesh of 2000-3000 mesh.
[0077] After the subsequent pulling and cutting tests are passed, the products will be packaged and put into storage.
[0078] Example 3 The copper alloy material for the relay spring and general electrical connectors achieved in this case has a width of 218 mm, a thickness of 0.64 mm, and a state of H04. The element composition, process parameters, and performance of this embodiment are shown in Tables 1 and 2.
[0079] The process used in this case is: batching, smelting, casting, sawing → hot rolling, milling → first cold rolling, trimming → cleaning → second cold rolling → first aging, first pickling and scraping → third cold rolling → second aging, second pickling and scraping → stretching, shearing, packaging and warehousing.
[0080] Ingredients. Ingredients are prepared in mass fractions. Cr, Zr and Si are introduced in the form of CuCr10 copper-chromium master alloy, CuSi20 copper-silicon master alloy and CuZr40 copper-zirconium master alloy.
[0081] Melting. First add CuSi20 copper-silicon master alloy, then add the same type of scraps, then add electrolytic copper, cover with graphite flakes, and the molten copper should not be exposed. When the temperature reaches the melting temperature of 1290℃, take samples to test the composition, and add CuCr10 copper-chromium master alloy and CuSi20 copper-silicon master alloy according to the test results. Let it stand for more than 20 minutes, take samples to test the composition, and after passing the test (if unqualified, add more and stand for more than 20 minutes), use inert gas, argon in this case, degas for 20-30 minutes, and the degassing flow rate is based on the covering layer jumping but not breaking to expose the copper water. Use dried graphite powder to cover tightly before casting, and the furnace mouth, crystallizer, launder, etc. should be baked red hot.
[0082] Casting. Casting temperature 1240℃, pulling speed 65mm / min, normal drawing speed 95mm / min, initial cooling water flow 30m3 / h, cooling water flow 70m3 / h, crystallizer vibration frequency 60 times / min, ingot size 180×610mm. During casting, the launder is covered with a covering agent composed of CaCO3, CaF2 and a small amount of MgCO3, and the crystallizer is protected by argon gas with a protective gas hood, and the argon gas pressure is [0.3,0.5]MPa.
[0083] The Zr element is added in the launder during the casting process.
[0084] The hot rolling temperature is 890℃, from 180mm to 17mm, the hot rolling processing rate is about 91%, 7 passes, and the processing rate of each pass is about 15%-45%. The hot rolled strip is cooled by water spraying, and the hot rolling is solid solution online.
[0085] Mill the surface to remove scale and various defects.
[0086] The first cold rolling is to 1.5 mm, the processing rate is about 90%, 9 passes, and the pass distribution is (unit: mm) 15→12→9.3→7.2→5.6→4.4→3.4→2.6→2→1.5.
[0087] The cutting edge retains a width of 610 mm.
[0088] After cleaning, the second cold rolling was performed to 0.88 mm, with a processing rate of about 41%. In this case, the second cold rolling was performed in 2 passes, with the pass distribution being (unit: mm) 1.5 → 1.12 → 0.88.
[0089] The first aging process is carried out after the second cold rolling. The bell jar aging process is carried out at 440℃, with an 11-hour heating process and an 8-hour insulation process. During the heating and insulation stages, the hydrogen content is 70%-80%, and the hydrogen flow rate is 8-20 cubic meters / hour. During the cooling stage, the hydrogen content is 70%-80%. The furnace temperature should not be greater than 60℃.
[0090] The first pickling and scraping. A large brush is used to press down the current, slow the cleaning speed, and use multiple pairs of brushes to grind off the Cr-rich oxide layer. The specific implementation parameters of different equipment are different. The equipment used for post-processing of the finished material in this case is specifically implemented as follows: cleaning at a speed of 35 meters per minute, the brush pressing current is 25A, the brush speed is 950 revolutions per minute, and the brush mesh is 2000-3000 mesh.
[0091] The third cold rolling was to 0.64 mm, with a processing rate of about 27%. In this case, the third cold rolling was carried out using a twenty-roller reversing mill, 2 passes, and the pass distribution was (unit: mm) 0.88→0.72→0.64.
[0092] The total processing rate of the second and third cold rolling in this case is about 57%.
[0093] The second aging process is carried out after the third cold rolling. The bell jar aging process is carried out at 420℃, with an 11-hour heating process and an 8-hour insulation process. During the heating and insulation stages, the hydrogen content is 70%-80%, and the hydrogen flow rate is 8-20 cubic meters / hour. During the cooling stage, the hydrogen content is 70%-80%. The furnace temperature should not be greater than 60℃.
[0094] Second pickling and scraping. Use a large brush to press down the current, slow the cleaning speed, and use multiple pairs of brushes to grind off the Cr-rich oxide layer. The specific implementation parameters of different equipment are different. The equipment used for post-processing of the finished material in this case is specifically implemented as follows: cleaning at a speed of 30 meters per minute, the brush presses down the current of 3.5A, the brush speed is 900 revolutions per minute, and the brush mesh is 2000-3000 mesh.
[0095] After the subsequent pulling and cutting tests are passed, the products will be packaged and put into storage.
[0096] Examples 4-10, Comparative Examples 1-17 The difference from Example 1 is that the alloy element composition is shown in Table 1.
[0097] Test Example 1 The copper alloy materials prepared in the above examples and comparative examples were tested, and the results are shown in Table 2.
[0098] The test methods for tensile strength, yield strength and elongation adopt GB / T 228.1 Tensile tests on metallic materials Part 1: Room temperature test methods.
[0099] The conductivity test method adopts YS / T 478 copper and copper alloy conductivity eddy current test method.
[0100] The Vickers hardness test method adopts GB / T 4340.1 Metal Vickers hardness test Part 1: Test method.
[0101] The fatigue performance test method adopts the JCBA T308 copper and copper alloy thin strip fatigue characteristics test method, in which the maximum stress is 300MPa.
[0102] Table 1
[0103] Table 2
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A copper alloy material, characterized in that: Calculated by mass percentage, it includes: Cr 0.15%~0.45%, Zr 0.05%~0.25%, Si 0.005%~0.05%, and the balance is copper and inevitable impurities; The mass ratio of Cr to Zr is (2:1) to (5:1); The mass ratio of Cr to Si is (10:1) to (30:1).
2. The copper alloy material according to claim 1, characterized in that: It also includes trace elements with a mass percentage of 0.001% to 0.15%; The trace elements include at least one of B, Mg, Ti, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y or Sc.
3. The method for preparing the copper alloy material according to claim 1 or 2, characterized in that: The following steps are involved: The materials are prepared according to the mass percentage, and then smelting, casting, hot rolling, first cold rolling, second cold rolling, third cold rolling and second aging treatment are carried out in sequence to prepare a copper alloy material; The first aging treatment is also included between the first cold rolling and the second cold rolling or between the second cold rolling and the third cold rolling.
4. The preparation method according to claim 3, characterized in that: The smelting temperature is 1270-1290°C; The casting process parameters include: casting temperature of 1220~1240°C, pulling speed of 55~65 mm / min, casting speed of 85~95 mm / min, cooling water flow of 45~70 cubic meters / hour, and crystallizer vibration frequency of 45~60 times / minute.
5. The preparation method according to claim 3, characterized in that: During the smelting process, it is covered with graphite flake covering agent; After smelting, it is covered with graphite powder covering agent and then cast; During casting, the launder is covered with a covering agent consisting mainly of CaCO3, CaF2, and MgCO3; During the casting process, the crystallizer is protected by protective gas; The Zr element is added during the casting process.
6. The preparation method according to claim 3, characterized in that: The hot rolling temperature is 880-960°C, and the hot rolled strip is cooled by water spraying; The processing rate of the hot rolling is 85% to 95%, and the processing rate of each pass is independently 15% to 45%.
7. The preparation method according to claim 3, characterized in that: The processing rate of the first cold rolling is 85% to 95%, and the processing rate of each pass is independently 20% to 25%; The total processing rate of the second cold rolling is 55% to 95%, and the total processing rate of the third cold rolling is 10% to 30%; The processing rate of each pass of the second cold rolling is independently 20% to 35%, and the processing rate of each pass of the third cold rolling is independently 10% to 30%.
8. The preparation method according to claim 3, characterized in that: The first aging treatment and the second aging treatment are bell jar aging treatments; The bell jar aging treatment includes: heating to 400-460°C for 10-12 hours, keeping the temperature for 7-9 hours, and then cooling to below 60°C before being taken out of the furnace; The bell jar aging treatment is carried out under a protective atmosphere.
9. The preparation method according to claim 3, characterized in that: After the first aging treatment and the second aging treatment, the chromium-rich oxide layer and oil stains are removed by pickling and scraping with a cleaning device; After the first aging treatment, the process parameters of pickling and scraping include: a cleaning speed of 20 to 35 m / min, a brush pressing current of 20 to 25 A, a brush speed of 700 to 950 rpm, and a brush mesh number of 2000 to 3000 meshes; After the first aging treatment, the process parameters of pickling and scraping include: a cleaning speed of 15 to 30 m / min, a brush pressing current of 0.6 to 3.5 A, a brush speed of 800 to 900 rpm, and a brush mesh size of 2000 to 3000 meshes.
10. Use of the copper alloy material according to claim 1 or 2 in the preparation of a relay reed or an electrical connector.